Gewalt in Laktanz' ›De mortibus persecutorum‹ - Zipp, Gianna (2021)
Violence is a central topic in De mortibus persecutorum, one of the most significant sources on the Tetrarchy's persecution of Christians. Gianna Zipp examines this piece of writing as a literary complete works and meticulously analyzes its conception using the method of close reading. She shows how Lactantius credibly portrays the violent Tetrarchs coming to their horrific end as determined by God.